Morphology and Development of Saprophagous Scuttle Fly, Spiniphora genitalis Schmitz, 1940 (Diptera: Phoridae) Larvae at Indoor Ambient Temperatures - Reena Abd Rashid; Raja M. Zuha (Tropical Life Sciences Research, 2025)
The oriental scuttle fly, Spiniphora genitalis Schmitz, 1940 (Diptera: Phoridae), was first discovered from Peninsular Malaysia as a specialised decomposer of mollusc carrion but its occurrences on vertebrate carrion suggest that this species could also be utilised as a forensic indicator. However, the larval morphology and development of S. genitalis remain unexplored. In this study, the colony of S. genitalis was reared in the laboratory at ambient temperature range (20.0oC–25.5oC) and relative humidity (71.0%–94.5%) using decomposing beef liver as larval food source. Larval body length was measured at every 6 h and 18 h interval until pupariation and subsequently described. The third instar larva of S. genitalis can be characterised by its fleshy, but ventrally flattened body with posterior tubular extension. The abdominal segments are covered with tubercles and spinulose formations and interestingly, three distinct larval variations were also detected. The transitions from metapneustic first instar to amphipneustic second and third instar larvae were also described according to the characteristics of cephalopharyngeal skeleton, anterior spiracle and posterior spiracle. The lifecycle of S. genitalis reported in this study based on it developmental stages were 23 h–27 h (egg), 162 h–358 h (larva) and 240 h–341 h (pupa). This study established the diagnostic features of S. genitalis which can be useful in forensic analysis and as precursors to the ground plan of Spiniphora larvae taxonomy. The complete growth of S. genitalis larvae on beef liver indicated that the role of this species has been expanded from a specialised mollusc carrion decomposer to a potential forensic indicator.